Hadith #42 - The Forty Hadith of Imam Nawawi - Anas ibn Malik (The Forty Hadith of Imam Nawawi)
I heard the Messenger of Allah (peace and blessings of Allah be upon him) say, “Allah the Almighty has said: ‘O Son of Adam, as long as you invoke Me and ask of Me, I shall forgive you for what you have done, and I shall not mind. O Son of Adam, were your sins to reach the clouds of the sky and you then asked forgiveness from Me, I would forgive you. O Son of Adam, were you to come to Me with sins nearly as great as the Earth, and were you then to face Me, ascribing no partner to Me, I would
Grade: Hasan